2023
DOI: 10.1007/s13239-023-00675-1
|View full text |Cite
|
Sign up to set email alerts
|

Is Accurate Lumen Segmentation More Important than Outlet Boundary Condition in Image-Based Blood Flow Simulations for Intracranial Aneurysms?

Abstract: Purpose Image-based blood flow simulations are increasingly used to investigate the hemodynamics in intracranial aneurysms (IAs). However, a strong variability in segmentation approaches as well as the absence of individualized boundary conditions (BCs) influence the quality of these simulation results leading to imprecision and decreased reliability. This study aims to analyze these influences on relevant hemodynamic parameters within IAs. Methods As a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…A splitting value was set at each outlet calculated with an in-house flow splitting method specific for each vessel model [ 35 ]. The splitting method was previously proofed to be stable and realistic [ 36 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…A splitting value was set at each outlet calculated with an in-house flow splitting method specific for each vessel model [ 35 ]. The splitting method was previously proofed to be stable and realistic [ 36 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…First, blood as a non-Newtonian fluid can be modeled with the Carreau model [80,119,154,155] or the Carreau-Yasuda model to mimic the non-Newtonian behavior [13]. Nevertheless, blood is mostly handled as Newtonian fluid with constant viscosity [15,16,156]. Berg et al, Fan et al and Razavi et al compared the impact of the choice of fluid modeling and found no significant difference between non-Newtonian and Newtonian blood composition in laminar flows [68,73,80].…”
Section: Three-dimensional Modelsmentioning
confidence: 99%
“…In older studies, specific blood pressure or a zero pressure condition is used [80,81,164]. In recent research, novel splitting approaches are applied to better mimic the outflow conditions [16,27,162]. Moreover, 0D resistance models are often used at the vessel outlets [1,68,117,165], which will be further examined in Section 4.2.…”
Section: Three-dimensional Modelsmentioning
confidence: 99%
See 2 more Smart Citations